The Association between Risk Factors and Blood Pressure in the Textile Industry Workers - Sumardiyono Sumardiyono; Hartono Hartono; Ari Probandari; Prabang Setyono (Universitas Islam Bandung, 2017)
Noise exposure is often found in the industrial environment that exposed workers at risk for increasing blood pressure. This study aimed at investigating the association between noise level, duration of noise exposure, age, use of earplugs, and body mass index with blood pressure on textile industry workers. An observational study with the cross-sectional design conducted during August to October 2016. The study population was 180 textile industry workers in Surakarta selected by consecutive sampling method. Statistical analysis used was multiple logistic regression. Results showed that variables associated with systolic blood pressure were the use of earplugs (OR=12.7), noise level (OR=7.2), body mass index (OR=5.3), age (OR=4.4) and duration of noise exposure (OR=3.5). Variables associated with diastolic blood pressure were the use of earplugs (OR=6.9), age (OR=6.6), noise level (OR=6.1), body mass index (OR=4.4), and duration of noise exposure (OR=3.1). In clonclusion, the risk factors for blood pressure increased among industrial workers are the use of earplug, noise level, body mass index, age and duration of noise exposure.ASOSIASI ANTARA FAKTOR RISIKO DAN TEKANAN DARAH PADA PEKERJA INDUSTRI TEKSTILPaparan kebisingan yang mengekspos pekerja sering ditemukan di lingkungan industri sehingga berisiko terjadi peningkatan tekanan darah. Penelitian ini bertujuan mengetahui hubungan tingkat kebisingan, durasi paparan kebisingan, usia, penggunaan sumbat telinga, dan indeks massa tubuh dengan tekanan darah pada pekerja industri tekstil. Penelitian ini menggunakan jenis observasional dengan desain cross-sectional yang dilakukan pada bulan Agustus–Oktober 2016. Populasi penelitian adalah pekerja industri tekstil di Surakarta. Terpilih 180 orang pekerja dengan menggunakan metode sampling konsekutif. Analisis statistik yang digunakan adalah regresi logistik berganda. Variabel yang berhubungan dengan tekanan darah sistole adalah penggunaan sumbat telinga (OR=12,7), tingkat kebisingan (OR=7,2), indeks massa tubuh (OR=5,3), usia (OR=4,4), dan durasi paparan kebisingan (OR=3,5). Variabel yang terkait dengan tekanan darah diastole adalah penggunaan sumbat telinga (OR=6,9), usia (OR=6,6), tingkat kebisingan (OR=6,1), indeks massa tubuh (OR=4,4), dan durasi paparan kebisingan (OR=3,1). Simpulan, faktor risiko peningkatan tekanan darah di kalangan pekerja industri tekstil adalah penggunaan sumbat telinga, tingkat kebisingan, indeks massa tubuh, usia, dan durasi paparan kebisingan.